(untitled) (Economics and region, 2019)
The article addresses the problem of increasing the national economy energy efficiency level. Analysis of the regulatory framework for the implementation of state policy towards ensuring energy efficiency of the Ukrainian economy is carried out. A dynamic analysis of a number of indicators for the state economic development in the context of determining the state and potential of energy efficiency of the national economy is characterized. A low degree of practical implementation of state measures on energy conservation and energy efficiency is noted. The main factors of restraining the national economy energy efficiency development are identified and a number of measures to increase its level are suggested.